Hiram Sharp: A Life Changed by the Battle of the Windmill - Patterson, Terrance (Ontario History, 2023)
Filled with a heightened sense of duty to eliminate the British from North America, Hiram Sharp, like many young Americans, joined a Hunters’ Lodge and fought with them in the Battle of the Windmill at Prescott where he was captured and then deportated to Van Diemen’s Land. His quest unfulfilled, Sharp ultimately forged a new path in another British colony at the far ends of the earth and helped bring about the form of democracy that both Canada and Australia share and enjoy today.